Biventricular longitudinal strain analysis using cardiovascular magnetic resonance feature-tracking: Prognostic value in Eisenmenger syndrome - Chao Gong; Chen Chen; Xuhan Liu; Ke Wan; Jiajun Guo; Juan He; Lidan Yin; Bi Wen; Shoufang Pu; Yucheng Chen (Journal of Cardiovascular Magnetic Resonance)
ABSTRACT: Background: Evidence to support risk stratification in Eisenmenger syndrome (ES) is still very limited. We hypothesized that biventricular longitudinal strain analysis could have potential prognostic value in ES. Methods: We prospectively enrolled 57 consecutive ES patients with post-tricuspid shunt who underwent both cardiovascular magnetic resonance (CMR) and right heart catheterization between June 2013 and March 2022. Biventricular longitudinal strains were evaluated by CMR feature-tracking analysis. The composite endpoint included all-cause mortality and re-admission for heart failure or hemoptysis. Cox regression analysis, Kaplan–Meier curves, and C-index were employed to assess the relationship between biventricular longitudinal strain and prognosis. Results: During a median follow-up of 33 months (interquartile range: 12–50), 35.1% (20/57) patients reached the composite endpoint. Patients with composite endpoints had significantly lower absolute values of left ventricular global longitudinal strain (LV GLS) and right ventricular free wall longitudinal strain (RV FWLS) than patients without composite endpoints (p < .05). Multivariate Cox regression analysis demonstrated that LV GLS and RV FWLS were independent predictors for composite endpoints (hazard ratio [HR]: 1.37, 95% confidence interval [CI]: 1.08–1.75, p = 0.010 and HR: 1.19, 95% CI: 1.01–1.41, p = 0.042). Kaplan–Meier analysis indicated that patients with both lower absolute values of LV GLS and RV FWLS were more likely to be at an even higher risk of composite endpoints (p <0.001). Furthermore, the combined addition of LV GLS and RV FWLS provided incremental value for the prognostic model including clinical parameters and biventricular ejection fraction (C-index increased from 0.75 to 0.86, p = 0.004). Conclusion: Impaired biventricular longitudinal strains improved prognostic prediction of ES patients with post-tricuspid shunt.